2010
DOI: 10.5137/1019-5149.jtn.3052-10.2
|View full text |Cite
|
Sign up to set email alerts
|

White fiber dissection of brain; the internal capsule: a cadaveric study

Abstract: AIM:This study was done to study the three dimensional anatomy of internal capsule's white fibers completely by cadaveric dissection and its relation to basal ganglia and other related anatomical structures. MATERIAL and METHODS: Eight formalin fixed cerebral hemispheres were dissected for internal capsule under operating microscope. Klingler's technique of fiber dissection was adopted. The internal capsule was dissected from superiolateral, inferior and medial surface of cerebral hemisphere. During and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The fibers entirely passed though the posterior limb of the internal capsule and external capsule. Previous studies showed that the superior and posterior thalamic radiation, which directly related to sensory, joined the posterior limb of the internal capsule [ 58 , 59 ]. Moreover, fibers passed through external capsule were generally considered to be involved in movement and coordination of movement [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fibers entirely passed though the posterior limb of the internal capsule and external capsule. Previous studies showed that the superior and posterior thalamic radiation, which directly related to sensory, joined the posterior limb of the internal capsule [ 58 , 59 ]. Moreover, fibers passed through external capsule were generally considered to be involved in movement and coordination of movement [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of regions ventral to both the STN and internal capsule, including the ventral hippocampus and amgydala, had little effect on motor function. Stimulation of the anterior internal capsule, which contains both motor tracts exiting the midbrain and sensory tracts from the thalamus to the pre-frontal cortex [33], resulted in hyperactivity with exacerbation of ipsilateral turning during high frequency stimulation. Stimulation of fibers within the anterior internal capsule may lead to sensory discomfort, or fear and panic [3435] that could increase ipsilateral turning in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of fibers within the anterior internal capsule may lead to sensory discomfort, or fear and panic [3435] that could increase ipsilateral turning in the rat. Stimulation of the posterior internal capsule, which contains the corticospinal tracts primarily carrying efferent motor signals [33], decreased both angular velocity and distance travelled. Stimulation of these fibers could result in muscle contractions, disrupting normal motor movements and causing the rat to freeze, resulting in decreased movement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sensory loss may also be associated with outcome and recovery [35]. Since the PLIC also contains sensory fibers, including fibers of the posterior thalamic radiation [36], PLIC-related anisotropy assessment may also reflect lesions affecting the sensory nervous system. In our study, patients with favorable outcomes and recovery also had better sensory function as quantified using the sensory item of the NIHSS.…”
Section: Discussionmentioning
confidence: 99%